Endocrinology Basic and Clinical Principles - Melmed, Shlomo; Conn, P. Michael; SpringerLink (Online service) (Totowa, NJ : Humana Press, 2005)
For this new edition of Conn & Melmed's Endocrinology: Basic and Clinical Principles, a panel of distinguished scientists and clinicians has completely rewritten every chapter to reflect the latest advances in our understanding of the endocrine system. Maintaining the original goal of the first edition to integrate the basic science of endocrinology with its physiological and clinical principles, the authors have succinctly summarized in 450 pages the latest findings on hormone secretion and hormone action, as well as all of the most recent insights into the physiology and pathophysiology of hormonal disorders. Coverage extends across the entire spectrum of endocrinology-from mammalian cells, plants, and insects to animal models and human diseases-with much increased coverage of diabetes and metabolism. Highlights include cutting-edge discussions of appetite disorders, obesity, reproductive failure, control of thyroid function, hormone action in humans and the lower species, and the mechanisms subserving hormone secretion. Concise yet comprehensive, Endocrinology: Basic and Clinical Principles, Second Edition offers students, clinicians, and scientists access to the entire spectrum of endocrinological knowledge, authoritatively illuminating the basic scientific principles underlying every aspect of hormone secretion and action, and leading the reader towards a full understanding of the pathogenesis and management of human endocrine disease.
to Endocrinology -- Hormone Secretion and Action -- Receptors -- Second-Messenger Systems and Signal Transduction Mechanisms -- Steroid Hormones -- Plasma Membrane Receptors for Steroid Hormones in Cell Signaling and Nuclear Function -- Growth Factors -- Prostaglandins and Leukotrienes -- The Neuroendocrine-Immune Interface -- Insects/Plants/Comparative -- Insect Hormones -- Phytohormones and Signal Transduction Pathways in Plants -- Comparative Endocrinology -- Hypothalamic-Pituitary -- Hypothalamic Hormones -- Anterior Pituitary Hormones -- Posterior Pituitary Hormones -- Endocrine Disease -- The Pineal Hormone (Melatonin) -- Thyroid Hormones (T4, T3) -- Calcium-Regulating Hormones -- Oncogenes and Tumor Suppressor Genes in Tumorigenesis of the Endocrine System -- Insulin Secretion and Action -- Cardiovascular Hormones -- Adrenal Medulla (Catecholamines and Peptides) -- Hormones of the Kidney -- Reproduction and Fertility -- Endocrinology of Fat, Metabolism, and Appetite -- Endocrinology of the Ovary -- The Testis -- Endocrinology of Aging.
Keywords: Medicine; Endocrinology; Medicine & Public Health; Endocrinology; Electronic books